Las Funciones Corporativas en el Grupo Empresarial Antioqueño durante la Última Década del Siglo XX (2019)
This article characterizes, from an administrative view, The Sindicato Antioqueño, de HQ of the same name modern business enterprise. The description is based on the main functions performed by this type of structure. The Sindicato Antioqueño's functions related with the portfolio definition, the external well as the internal administration, are described for the last decade of the XXth century, period defined by an open economy.